Prospecção molecular e análise funcional de short-peptides vegetais - Jucá, Thiago Lustosa (2014)
An increasing number of peptides isolated from a range of tissue plants have highlighted these molecules as a potential study target. Those peptides demonstrate a large functional variety and, therefore, have been frequently described in the scientific literature of the last years. The present work reports a molecular prospecting and functional characterization of plant "short-peptides". Initially, the Calotropis procera latex was partitioned into five fractions: hexane (49.4%), dichloromethane (5.2%), ethyl acetate (2.0%), butanol (2.1%) and aqueous (41.1%) (Chapter 1). The phytochemical profile and the spectroscopic analysis showed that the dichloromethane fraction was chemically the most heterogeneous. The dichloromethane and ethyl acetate fractions showed in vitro cytotoxicity against tumor cell lines (LD50 ranging from 0.05 to 3.9 mg/mL) and in vivo citotoxity against the crustacean Artemia salina (LD50 ranging from 10.9 to 65.7 mg/mL). These same fractions showed anti-inflammatory activity in carrageenan-induced peritonitis model in rats, associated to an inhibition of neutrophil migration for the dichloromethane (67%) and ethyl acetate (56%) fractions. A positive reaction with tolidine and ninhydrin suggests the presence of cyclopeptides in the bioactive ethyl acetate fraction. In Chapter 2, twenty primary sequences of peptides derived from the 1 fraction of Jatropha curcas seeds were deduced by de novo sequencing and confirmed by searches against genomic Jatropha database. The comparison of MS/MS fragmentation patterns between the doubly charged ion (671.79 m/z) found in fractions 1 and PII-C and its analogue synthetic peptide has shown that the use of additional analytical steps for the identification and characterization of these peptides would be not necessary. The BlastP search tool showed that the sequence APTLSGGSVPRDAD is homologous to and it is inserted into the conserved domain of the late embryogenesis protein (LEA_6). In Chapter 3, the two analogues synthetic peptides, linear (1342.44 g/mol) and cyclic (1324.44 g/mol), obtained by solid phase synthesis, showed differences that characterize their arrangement when compared to the pattern fragmentation by MS/MS and ion mobility. The net charge and the retention time had similar physicochemical parameters in both peptides. Dichroism circular studies showed the presence of a disordered state to both peptides. The biological assays of peptides showed no apparent signs of functional activity, however this fact do not exclude the possibility to test additional biological models. The results arising from this study generate new prospects and provide a basis for further work aiming the isolation and characterization of peptides in C. procera and J. curcas species.